New economic policy, workplace and human development - Mehta Prayag
The new economic policy(NEP) is be implemented in the country wiith the claim to make the Indian industry more competitive. Such competitiveness has, however to be obtained in the society and at the workplace where the productive energy of the people has to be released for greater innovativeness and creativity. With the growing unemployment in the country and the threatened `exit and downsizing' which is likely to result under privatisation. The society, as a whole, and the workplace, in particular may have to suffer moral and mental health problems. These would suck into the self-esteem and self-efficacy of workers and would, thus directly hit their skills capabilityand human development
Keywords: New Economic Policy -- India; India -- Economic Policy